Processes of excitation energy transport in EuPO4 and EuP3O9 nanocrystals - Kononets, N.V.; Seminko, V.V.; Maksimchuk, P.O.; Aslanov, A.V.; Bespalova, I.I.; Masalov, A.A.; Malyukin, Yu.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Processes of excitation energy transport were investigated for EuPO4 and EuP3O9 nanocrystals, in which Eu3+ ions form three- and one-dimensional subsystems, respectively. It was determined that for EuPO4 nanocrystals 5D0 luminescence quenching manifested itself even at low temperatures due to effective phonon-assisted energy migration. At the same time, for EuP3O9 nanocrystals no influence of energy migration on the luminescence quenching was observed in the whole temperature range from 10 to 293 K that can be ascribed to modification of phonon spectra for EuP3O9 nanocrystals as compared to their bulk counterparts.